FREQUENCY, DISTRIBUTION OF SUBTYPES AND IMMUNOHISTOCHEMICAL PROFILE OF NON-HODGKIN LYMPHOMA IN PAEDIATRIC AND ADOLESCENT PATIENTS - Jamal, Saba; Mansoor, Neelum; Kaleem, Bushra; Lateef, Fouzia; Yaqoob, Nausheen (Journal of Ayub Medical College Abbottabad, 2022)
Background: Non-Hodgkin lymphoma is a common malignant disorder in paediatric and adolescent age group. There is a need of large-scale studies to understand the disease pattern in Pakistan as no official registry exist in most of the developing countries. This study comprised a large cohort of 223 patients, spanned over a decade from January 2008-December 2019 and aimed to report the prevalence of subtypes, demographics and immunohistochemical profile from this region. Methods: Retrospective study, conducted at Indus hospital and health network and Ziauddin university hospital, Karachi, Pakistan. Sequential data analysis was carried out on all consecutive samples including both needle and excisional biopsies of patients below 18 years of age. Morphological examination of H&E stained sections along with immunohistochemistry is performed in order to identify subtypes and immunophenotypic patterns using an extensive panel of markers. Results: Our results demonstrate 66% B-cell lymphomas while 34% T-cell lymphomas. Overall male to female ratio was 3.3:1 with median age 8 years (1.1-17 years). Among B-cell lymphoma, Burkitt lymphoma is most common while in T-cell, T-lymphoblastic lymphoma is the most common subtype. In anaplastic large cell lymphoma category, null cell phenotype was predominant, i.e., 65%. T-NHL frequency is found to be higher in our population. However, results of immunohistochemistry are similar to published literature. Conclusion: The study will help to identify disease patterns in terms of subtypes of NHL and its immunohistochemical profile that plays a vital role in diagnostic, prognostic and therapeutic implications.